1998
DOI: 10.1029/98gl01055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of E‐region electric fields observed with a sounding rocket and a Doppler radar in the Seek Campaign

Abstract: Abstract. This paper describes results from simultaneous measurements of mid-latitude irregularities by a sounding rocket and a Doppler radar. The experiment was conducted on August 26, 1996 as part of the SEEK (Sporadic-E Experiment over Kyushu) campaign in Japan. Electric field observed with a doubleprobe sensor on the rocket showed very large fluctuations of 4-10 mV/m where irregularity echoes were quite intense. Doppler velocities observed with the radar agreed well with the electric fields. We estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
4
12
0
Order By: Relevance
“…As far as the neutral wind shear driven KHI is concerned, Larsen [2000], based on the simulation studies of KHI made by Fritts et al [1996], showed that the timescale for the build up and restabilization of the shear flow is ∼30 min, which means that if the shear instability is the seed for the gradient drift instability, QP event should be observed for about 30 min at a time and this could repeat as long as the shear flow repeats. Some of the midlatitude QP events occurring in a condition of large wind shear have been found to occur in patches with temporal spacings of 40–60 min [ Yamamoto et al , 1998; Larsen et al , 1998], which are quite consistent with that expected from KHI. The QP echoes that we observed, however, continued to occur for 2–8 h. Thus it is not clear as to how the QP striations should occur continuously for such a long period if they were to be associated with KHI.…”
Section: Discussionsupporting
confidence: 61%
“…As far as the neutral wind shear driven KHI is concerned, Larsen [2000], based on the simulation studies of KHI made by Fritts et al [1996], showed that the timescale for the build up and restabilization of the shear flow is ∼30 min, which means that if the shear instability is the seed for the gradient drift instability, QP event should be observed for about 30 min at a time and this could repeat as long as the shear flow repeats. Some of the midlatitude QP events occurring in a condition of large wind shear have been found to occur in patches with temporal spacings of 40–60 min [ Yamamoto et al , 1998; Larsen et al , 1998], which are quite consistent with that expected from KHI. The QP echoes that we observed, however, continued to occur for 2–8 h. Thus it is not clear as to how the QP striations should occur continuously for such a long period if they were to be associated with KHI.…”
Section: Discussionsupporting
confidence: 61%
“…From the rocket observations it was found that the E s layers were horizontally stratified rather than modulated in altitude as proposed by Woodman et al [1991]. On the other hand, they found very large electric fields of more than 10 mV m −1 and very large wind shear in the lower E ‐region associated with the QP echoes [ M. Yamamoto et al , 1998; M.‐Y. Yamamoto et al , 1998; Nakamura et al , 1998; Pfaff et al , 1998; Larsen et al , 1998].…”
Section: Introductionmentioning
confidence: 83%
“…The instability characteristics are consistent with the morphology of QP echoes, which are coherent radar echoes associated with E s layers that occur in the midlatitude region during summer nights [ Yamamoto et al , 1991, 1992], when the field‐line‐integrated Hall conductivity would be most likely to dominate. The mean Doppler velocities associated with QP echoes imply electric fields of 3–5 mV/m [ Yamamoto et al , 1998]. Furthermore, the Doppler spectrum often has a very broad spread, exceeding ±200 m/s, which may indicate that small scale electric fields can approach 10 mV/m.…”
Section: Introductionmentioning
confidence: 99%